An Experimental study on the physico-mechanical properties of coconut palm phellem (COPAP) drywall board as construction material - Osio, Arnulfo Miguel C.; Juanga, Jean Marie V. (2020)
The production of wood-based boards is projected to cover a forest with 521 million cubic meters by the end of 2030. The increasing demand of wood threatens the supply for the future generation to use. This project aimed to develop a drywall panel board made from coconut palm phellem as an alternative material of wood. The phellem is the outermost layer of stems and roots which and is considered as bio-waste by the wood construction industry. It is a natural and renewable product - it can be extracted directly from living plants without affecting its life. It has high coefficient of friction, resilience, thermal properties, slow burn rate, shock absorption capacity, high energy absorption, excellent insulation properties and near-zero Poisson coefficient making it the optimum material for variety applications. COPAP board physico-mechanical properties were tested to determine its application and were compare to othercommercially available materials. The wood wool drywall board production was followed by the researcher which is done with the use of cement and a raw material. Three different formulations were used to determine the best formula to produce COPAP board. These formulas differed in the percentage of coconut palm An Experimental Study on the Physico-Mechanical Properties of Coconut Palm Phellem (COPAP) Drywall Board as Construction Material phellem and cement by weight used. The Formulation A, Formulation B, and Formulation C have a mixture of 40% COPAP and 60% cement, 25% COPAP and 75% cement, and 10% COPAP and 90% cement, respectively. The study showed that the physico-mechanical properties increases as the volume of the phellem in the formula decreases except for water absorptivity rate as it decreases together with the phellem volume. Formulation C emerged as the best formulation of COPAP board. Finally, the study concluded that the final product can only be used for interior partitions or non-load bearing walls and not for flooring, ceiling, and other horizontal applications.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020